Analisis Pengaruh Kualitas Produk dan Citra Merek Terhadap Keputusan Pembelian Produk Glad2Glow di E-Commerce Shopee - Hanum Wahda Zuhriyah; Ita Rahmawati (Fakultas Ekonomi Universitas KH. A. Wahab Hasbullah, 2026)
This study aims to analyze the influence of product quality and brand image on purchasing decisions for Glad2Glow products on the Shopee e-commerce platform. The study employed a quantitative approach involving 100 respondents selected using a purposive sampling technique. The respondents met the following criteria: consumers aged 15–44 years, had purchased Glad2Glow products through Shopee at least once, and owned a Shopee account through which they independently made purchases, enabling them to evaluate the product quality and brand image. Data were collected using a questionnaire and analyzed using multiple linear regression with SPSS Statistics 27. The results indicate that, partially, product quality has a positive but insignificant effect on purchasing decisions (t = 0.844; p = 0.401), whereas brand image has a positive and significant effect (t = 5.065; p < 0.001). Simultaneously, product quality and brand image have a significant effect on purchasing decisions (F = 67.123; p < 0.001). The coefficient of determination (R²) of 0.581 indicates that product quality and brand image explain 58.1% of the variance in purchasing decisions, while the remaining 41.9% is influenced by other factors not examined in this study. This study is limited by its relatively small sample size and its focus solely on consumers who have purchased and used Glad2Glow products through the Shopee platform.